Communication Dynamics and the Transformation of Martial Arts Educational Values: The Role of Group Conformity and Demographic Factors in Shaping Aggressive Behavior - Banu Prasetyo; Henri Subiakto; Yuyun Wahyu Izzati Surya; Rika Adi Kusumo; Ulfa Arofah; Quarin Hadianita (Jurnal Pemberdayaan Masyarakat, 2026)
Martial arts education is not only a physical training process but also a social learning environment where communication, group interaction, and shared norms shape students' behavior. Within martial arts communities, conformity to group norms may influence how students interpret discipline, courage, and aggression. This study aims to examine the influence of group conformity and demographic characteristics (age and gender) on aggressive behavior among martial arts students in East Java. Using a quantitative survey design, data were collected from respondents through a validated Likert-scale questionnaire. Multiple linear regression analysis was used to test the influence of the independent variables. The findings show that conformity has a negative, statistically significant effect on aggressive behavior, suggesting that adherence to positive group communication norms can reduce aggression. Age shows a positive and significant effect, while gender does not have a significant partial effect. Simultaneously, conformity, age, and gender explain the variance in aggressive behavior. These findings highlight the importance of communication dynamics and positive group norms in martial arts training environments as mechanisms for reducing aggressive tendencies among students.